Liparis mai (Orchidaceae; Malaxideae), a new species from China: evidence from morphological and molecular analyses - Tu, Xiong-De; Huang, Ming-Zhong; Liu, Ding-Kun; Ma, Liang; Li, Ming-He (Phytotaxa, 2020)
A new species, Liparis mai (Malaxidinae, Epidendroideae, Orchidaceae), from Guangxi, China, is illustrated and described based on morphological and molecular analyses. This new species is similar to L. nervosa but differs by the older pseudobulb often bearing bulbil, larger revolute lateral sepals, obovate-elliptic lip and caniniform callus. Molecular analyses of nuclear (ITS) and plastid (matK) DNA support L. mai as a distinct species, which forms an independent lineage sister to L. nervosa and its allies.